IMPLEMENTATION OF ACTIVE LEARNING METHOD IN IMPROVING UNDERSTANDING OF MORAL MATERIAL ON STUDENTS AT SCHOOL - Muchlis, Achmad Khoirul; Turmudi, Imam; Puspitarini, Dwi (Islamic Management: Jurnal Manajemen Pendidikan Islam, 2025)
This study aims to explore the implementation of active learning methods in improving students' understanding of moral material at school. Active learning is a learning approach that emphasizes students' active participation in the teaching and learning process. In this study, various techniques such as group discussions, simulations, and case studies were used to encourage student engagement. The results show that this method is effective in improving students' understanding of moral concepts, creating an interactive learning atmosphere, and building critical thinking skills. The findings provide important implications for the development of morals learning methods in schools.